Money, banking, and old-school historical economics - Eric Monnet; François R. Velde (Federal Reserve Bank of Chicago, 2020)
We review developments in the history of money, banking, and financial intermediation over the last twenty years. We focus on studies of financial development, including the role of regulation and the history of central banking. We also review the literature of banking and financial crises. This area has been largely unaffected by the so-called new econometric methods that seek to prove causality in reduced form settings. We discuss why historical macroeconomics is less amenable to such methods, discuss the underlying concepts of causality, and emphasize that models remain the backbone of our historical narratives. Keywords: historical macroeconomics, money, banking, financial intermediation.
Keywords: N01; N10; N20; 330; Geldgeschichte; Finanzintermediation; Zentralbank; Makroökonomik